The Influence of Profitability, Liquidity, and Managerial Ownership on Firm Value with Dividend Policy as a Mediating Variable - W.D. Waleri; Jeudi A.T.P. Sianturi; Winarto Winarto (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The goal of this research is to elucidate how dividend policy contributes to the relationship between business valuation and profitability levels. Purposive sampling is used in this study to choose 22 logistics and transportation companies that are listed on the Indonesia Stock Exchange between 2019 and 2023. Version 8.0 of the WarpPLS program was used to analyze the data. The study's findings suggest that business value is positively impacted by management ownership, liquidity, and profitability. Profitability has a favorable impact on dividend policy, which serves as a bridge connecting profitability and business value.